Profile of Creative Thinking Skills and Analysis of Students' Perceptions of Physics Learning - Elvira Clarita Melur; Winny Liliawati; Achmad Samsudin; Lina Aviyanti; Andy Setiawan (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to describe the profile of students' creative thinking skills in Physics and analyze their perceptions of Physics learning. The method used is descriptive quantitative involving 59 high school students selected through random sampling techniques. The instruments used include creative thinking skills tests and student response questionnaires that are analyzed using descriptive statistics. The results of the study indicate that in general students' creative thinking skills are in the moderate category with an analysis per aspect, where "originality" obtained the highest percentage, while "flexibility" showed the lowest value. There was no significant difference between the creative thinking skills of male and female students. From the results of the questionnaire, some students stated that Physics lessons were still considered difficult and the learning was less innovative. Although most students have experience in working on projects, the implementation of mini projects is still considered necessary to optimize the development of creative thinking skills. These findings can be the basis for further research in developing project-based learning models to improve students' creative thinking skills in Physics learning in high school